Ergonomic evaluation of the GPS message display terminal used in Singapore taxis - Sulistyawati, Ketut (Animo Repository, 2005)
A Global Positioning System (GPS) for taxi booking is currently being used in Singapore to enhance the effectiveness of taxi booking and dispatching.. The system comprises a central coordinating headquarters and mobile reception terminals in taxis called Mobile Display Terminals (MDT's). These terminals are placed next to the taxi dashboard to the left of the drivers and are used to display messages sent from the headquarters to the driver. As both the MDT and driving tasks are visually demanding, appropriate design of the device is vital to ensure safety. For this reason, the design of the MDT has been evaluated through observations and interviews with taxi drivers. Three different MDT's in use in Singapore have been assessed in terms of their display design and usability. In addition, the advantages and disadvantages of a GPS MDT are compared against the preceding radio based system. The results of the analysis suggest that the MDT is effective in conveying information to the driver. More recent designs that use color, icons, and issues that remain unaddressed by these designs, such as overlapping buttons, obscure icons, menu arrangement, and screen luminance. Specific recommendations to improve the existing systems are presented in this paper. Keywords: GLobal positioning system, taxi booking, message display terminal, safety, usability